Global and Local Operations of Finnish Metal Industry Companies during COVID-19 and Trade Disruptions: A Case Study - Pasi Rönkkö; Jere Lehtinen; Jukka Majava; Pekka Tervonen (International School for Social and Business Studies, 2021)
Purpose: Globally operating companies have been disrupted by many simultaneous crises in recent years, specifically the COVID-19 pandemic, Brexit, and trade wars. This study identifies the key factors in companies' decisions to expand their global supply chains or to operate more locally in today's world. Study design/methodology/approach: This article contains a literature review and empirical study. Representatives from three Finnish B2B manufacturing companies in the metal industry were interviewed about their international and local operations. Findings: The key reasons for global operations included a large supplier base, component availability, lower costs, and specialised products. Typical problems included quality issues, long lead times, and communication challenges. Specific risks and mitigations around COVID-19, Brexit, and trade wars are also presented. Originality/value: The study provides updated information on global and local operations. Unique reasons for global operations included manufacturing Engineer-to-Order (ETO) products close to the customer and changes in products.